DESIGN OF SAUCER AS A DRINKING TOOL FOR PARKINSON'S PATIENTS USING MORPHHOLOGICAL METHOD - Icha Mutiara Addeni; Ribangun Bamban Jakaria (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Almost all humansuse glasses to make it easier for them to drink. No wonder there are so many glass products on the market with various designs. People with parkinson’s cannot use glasses properly, because they have movement disorders so that when they hold the glass, the water in it will spill. Seeing from the existing problems, it is necessary to design a saucer as a drinking aid. Which of course will make it easier for them to use glasses. In the design of the saucer using the morphological method. One of the methods commonly used in evaluating design concepts. The results of the selection process for the combination of components that make up this saucer, it can be concluded that from the selection process using the morphological method, the most appropriate saucer is to use concept 3 with score of 12,6, where the design is ranked 1.